2016
DOI: 10.1108/yc-09-2015-00558
|View full text |Cite
|
Sign up to set email alerts
|

Fashioning masculinity among young New Zealand men: young men, shopping for clothes and social identity

Abstract: Article information:To cite this document: Lisa McNeill Jacob McKay , (2016),"Fashioning masculinity among young New Zealand men: young men, shopping for clothes and social identity", Young Consumers, Vol. 17 Iss 2 pp. -Permanent link to this document: http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
(66 reference statements)
2
18
0
1
Order By: Relevance
“…The study adds to the existing research on green apparel purchases by examining the role of cosmopolitanism, global self-identity and online brand communities in predicting Indian consumers’ evaluation of green apparel. It extends the previous work on self-identity and social identification (Cleveland et al , 2014; McNeill and McKay, 2016) in evaluating green apparel’s perceived intrinsic and extrinsic product attributes. It demonstrates that consumers’ preferences for green clothing are affected by a desire to show conformity to traits of cosmopolitanism and global self-identity.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The study adds to the existing research on green apparel purchases by examining the role of cosmopolitanism, global self-identity and online brand communities in predicting Indian consumers’ evaluation of green apparel. It extends the previous work on self-identity and social identification (Cleveland et al , 2014; McNeill and McKay, 2016) in evaluating green apparel’s perceived intrinsic and extrinsic product attributes. It demonstrates that consumers’ preferences for green clothing are affected by a desire to show conformity to traits of cosmopolitanism and global self-identity.…”
Section: Discussionsupporting
confidence: 69%
“…Dashper and St. John (2016), found that formal competition dress in the regular sporting activities was important in bestowing an individual sporting identity and represented the peculiar ethos of equestrian sport. McNeill and McKay (2016), in their research on young males’ perception of fashion clothing and its role in social identity construction, indicated the influence of social comparison on fashion-seeking behavior. Kelly (2010), in her study on Muslim women in Kuwait, found that dress was an important criterion for exhibiting success and status.…”
Section: Introductionmentioning
confidence: 99%
“…Media objectification creates a desire of self-gratification which ultimately leads toward achieving those desire by purchasing the clothes. These results are supported by existing studies (McNeill, McKay, 2016;Stuart, Kurek, 2019;Veer, Golf-Papez, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Kautish and Sharma (2018) found that fashion consciousness significantly affects consumers' online try-on behavior and their frequency and willingness to buy clothing online. This shopping enjoyment is derived from the fact that it is often necessary for consumers with high fashion consciousness to satisfy the pursuit of body image consciousness consumption by online try-on experience and online purchase of clothing (Kautish and Sharma, 2018;McNeill and McKay, 2016). Ladhari et al (2019) further found that college students (over 19 years old) not only have high fashion consciousness but also like to use digital technology to try on.…”
Section: Moderating Effect Of Fashion Consciousnessmentioning
confidence: 99%